Hérnia de Morgagni simulando lipoma torácico - Elias Amorim; Jairo de Sousa Pacheco (Revista do Colégio Brasileiro de Cirurgiões)
The Morgagni hernia is the rarest kind of diaphragmatic hernia , occurring in 3% of all cases. It consists of the protrusion of the abdominal content into the thoracic cavity including omentum and transverse colon, among others. It is more common in the right side and appears more frequently after 40 years of age or after a raise in the intra-abdominal pressure. Patients with Morgagni hernia are usually asymptomatic. In the X-ray it appears like an opaque image in the cardiophrenic angle.Surgical correction is the treatment of choice for this conditions. We present one case of Morgagni hernia successfully treated.